A gendered lens to self-evaluated and actual climate change knowledge - Sammie, Batanai; Mupfiga, Elvis; Mwadzingeni, Liboster; Chitata, Tavengwa; Mugandani, Raymond (Journal of Environmental Studies and Sciences, 2021)
Gender-sensitive and gender-responsive approaches are important to increase adaptive capacity in a changing climate given the gendered nature of exposure levels to climate shocks. Nonetheless, knowledge and perception of the public to climate change influence behavioural intention to adapt. While literature is replete with public perception and adaptation strategies to climate change, there is a dearth of information exploring the influence of gender on climate change knowledge. This paper employs quantitative and qualitative data to examine the influence of gender on knowledge in climate trends in Beitbridge Rural District, Zimbabwe, using questionnaire surveys. This survey tool consisted of demographic questions on gender and other variables. Our results indicate that compared to women, actual knowledge of trends in selected variables of climate change was higher among men. Furthermore, male respondents had higher self-evaluated knowledge on climate trends compared to female participants.We recommend gender disaggregated data in the vulnerability and adaptation assessments and the education, training and awareness sections of the National Communications to the United Nations Convention on Climate Change.